Sensor Stream Reduction - Aquino, Andre L.L.; Filho, Paulo R.S. Silva; Wanner, Elizabeth F.; Rabelo, Ricardo A. (Intelligent Sensor Networks, 2013)
This chapter introduces a methodology for sensor stream reduction in wireless sensor networks. Considering a sensor stream reduction application, a basic methodology is composed of four phases: characterization, reduction tools, robustness, and conception. The data reduction process, in this conceptual model, consists of the sensed data characterization, that is, how the data can be collected and represented, and the application specification, that is, what application requirements have to be considered, for example, real-time deadlines, energy consumption, or QoS guarantee. The sensing reduction is recommended when the sensor device gets an excessive number of samples, and be dynamically calibrated to deal with more data than it currently deals with. The routing reduction, in contrast, is performed when the network does not support the amount of data being transmitted. A group of reduction solutions must be available to help the application development.